PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP EKUITAS MEREK YANG DIMEDIASI OLEH CITRA PERUSAHAAN - Pratama, Gede Wibi Satya; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 5 No 7 (2016), 2016)
In carrying out its activities the company should have a sense of responsibility towards environmental sustainability. Businesses in Indonesia are required to run his business with a responsible one through the activities of corporate social responsibility (CSR). The purpose of this study was to clarify the effect of CSR and corporate image of the brand equity, explained the influence of CSR to the corporate image, and explains how the role of the corporate image in mediating the effects of CSR on brand equity.The study was conducted at Astra Honda motorcycle products in Denpasar, the number of respondents in this study were 100 people. The data obtained through direct questionnaires were then analyzed using path analysis (path analysis). From the test results showed that corporate social responsibility significant positive effect on brand equity, corporate social responsibility significant positive effect on the corporate image, corporate image significant positive effect on brand equity and corporate image mediates the influence of corporate social responsibility which impact on increasing brand equity on the product Astra Honda in Denpasar.
Keywords: corporate social responsibility, corporate image, brand equity